Report on the First Nigerian Economic Summit 18 - 20 february, 1993 (Ibadan Spectrum Books Ltd, 1993)
This report is a stunning, incisive and frank appraisal of the Nigerian condition covering politics, the economy, law and order and accountability. it is the most objective assessment of the Nigerian economy ever published.
osc 19/8/16
Loans
Keywords: Dozie, pascal; Bickersteth, oluseyi; Economic Situation; Nigeria